Vascular Access Perspectives in Patients After Kidney Transplantation - Letachowicz, Krzysztof; Banasik, Mirosław; Królicka, Anna; Mazanowska, Oktawia; Gołębiowski, Tomasz; Augustyniak-Bartosik, Hanna; Zmonarski, Sławomir; Kamińska, Dorota; Kuriata-Kordek, Magdalena; Krajewska, Magdalena (Frontiers in Surgery, 2021)
Introduction: More attention has been paid to the influence of arteriovenous fistula (AVF) on the cardiovascular system. In renal transplant recipients some beneficial effect of elective vascular access (VA) ligation was observed in patients with high AVF flow. The aim of our study is to elucidate vascular access function and VA perspective in the kidney transplantation (KTx) population. Materials and methods: KTx patients with stable graft function were recruited to participate in this single center observational study (NCT04478968). The measurement of VA flow (Qa) and vessel mapping for future vascular access was performed by color Doppler ultrasound. The study group included 99 (63 %) males and 58 (37 %) females; median age was 57 (IQR 48-64) years. The median time from transplantation to baseline visit was 94 (IQR 61-149) months. Median serum creatinine concentration was 1.36 (IQR 1.13-1.67) mg/dl. Results: Functioning VA was found in 83 of 157 (42.1 %) patients. The sites were as follows: snuffbox in 6 (7.2 %), wrist in 41 (49.4 %), distal forearm in 18 (21.7 %) patients, middle or proximal forearm in 8 (9.6 %), upper-arm AV graft in 1 (1.2 %), and upper-arm AVFs in 9 (10.8 %) patients, respectively. Blood flow ranged from 248 to 7830 ml/min, median 1134 ml/min. From transplantation to study visit 66 (44.6 %) patients experienced access loss. Access loss occurred within first year after KTx in 33 (50 %) patients. Majority (50 of 83, 60.2 %) of patients with active VA have options to create snuffbox or wrist AVF on contralateral extremity. In a group of 74 patients without functioning VA creation of snuffbox or wrist AVF on non-dominant and dominant extremity was possible in 7 (9.2 %) and 40 (52.6 %) patients.Access ligation was considered by 15 of 83 (18.1 %) patients with patent VA. Conclusions: Blood flow in majority of patients was below the threshold of the negative cardiovascular effect of vascular access. Creation of distal AVF is protective measure to avoid high flow and preserve vessels for future access. The approach to VA should be individualized and adjusted to patient’s profile.